Thermal and compressional behavior of the natural borate kurnakovite, MgB3O3(OH)5·5H2O. (10th January 2021) - Pagliaro, Francesco; Lotti, Paolo; Battiston, Tommaso; Comboni, Davide; Gatta, G. Diego; Cámara, Fernando; Milani, Sula; Merlini, Marco; Glazyrin, Konstantin; Liermann, Hanns-Peter
Graphical abstract: Highlights: Kurnakovite can be adopted as neutron-radiation absorber in concretes and tiles. Its thermal and compressional behaviors have been studied by in situ XRD. Dehydration-induced structural collapse occurs at T  > 393 K. At high- P, kurnakovite is stable under the conditions for any technical utilization. Refined bulk α V and β V at ambient conditions: 5.18(1)·10 −5 K −1 and 0.029(2) GPa −1 . Abstract: The thermal and compressional behaviors of kurnakovite, a potential B-rich aggregate in neutron radiation-shielding concretes, were studied by in situ single-crystal synchrotron X-ray diffraction (100–393 K, 0–13.36(5) GPa). Above 393 K, the crystal structure collapses in response to dehydration. The bulk thermal expansion coefficient is α V (298K)  = 5.18(1)∙10 −5 K −1 . Volume compressional trend modelled with a Birch-Murnaghan equation of state yields a bulk modulus of K P0, T0  = 35(3) GPa. A phase transition occurs between 9.23(5) and 11.11(5) GPa, leading to a triclinic high- P polymorph (with triple unit-cell volume) and to an increase in coordination of one third of the trigonal-planar boron sites to a tetrahedral geometry.